SUCCESSFUL LANGUAGE LEARNING STRATEGIES USED BY SUCCESSFUL YEAR 5 ENGLISH AS A SECOND LANGUAGE (ESL) LEARNERS - Peter Lee Pui Weng; Melor Md Yunus; Mohamed Amin Bin Embi (Proceedings of The ICECRS, 2016)
Research on language learning strategies in Malaysia has been carried out extensively since mid 1990s. However, these studies have not covered the language learning strategies among native pupils in suburban primary school in Mukah, Sarawak. The main objective of the study was to identify the language learning strategies used by English as Second Language (ESL) learners. Data was collected using a survey questionnaire with 20 outstanding Year 5 ESL Iban learners in one of the suburban schools in Mukah, Sarawak. The instrument used in this study include a Language Strategy Use Questionnaire adapted from Language Strategy Use Inventory by Cohen, Oxford and Chi (2002). The adapted version of Language Strategy Use Questionnaire consists of 60 statements concerning the four major English language skills, namely listening, speaking and reading as well as acquisition of vocabulary and grammar. Data was analyzed through mean, frequency, percentage and standard deviation. The findings revealed that these learners were moderate users of listening, reading, writing, grammar and vocabulary strategies and low users of speaking strategies. There were variations in responses with regard to the use of language learning strategies among primary school learners. The pedagogical implications of the findings are also discussed.